Nazis, Islamists, and the Making of the Modern Middle East - BARRY RUBIN, WOLFGANG G. SCHWANITZ (Yale University Press, 2014)
The story of Nazi Germany’s involvement in the Middle East has hitherto largely been viewed as a dramatic tale of might-have-been that was nevertheless marginal to Middle East history and the course of World War II. In fact, however, this episode was central to the modern history of the Middle East and continues to reverberate many decades later given its profound effects on Arab nationalism, Islamism, and the course taken by the Palestinian Arab movement. The recent release by the U.S. government of massive quantities of both wartime and postwar documents coupled with the translation of previously unused German documents and Arabic-language accounts permits a much fuller telling of the story of the interactions among Arabs, Muslims, and Germans. To understand this history requires bringing together several elements. First, there was the German strategy, beginning in the late nineteenth century, that saw Berlin’s interests in the Middle East as being linked to an Islamic jihad against Germany’s European rivals conducted with the help of Muslim organizations. On the other side were radical forces of nationalism and Islamism in rebellion against the regional status quo. These latter groups would become not merely Nazi Germany’s protégés but its partners due to common interests and a set of parallel ideas. This was, then, neither purely an alliance of convenience nor a situation in which the Nazis were the teachers and the Middle Easterners were the pupils. Beyond the world war itself and the collapse of Nazi Germany these events were to have long-term ramifications for Middle Eastern history going far beyond 1945. The Middle East was the only part of the world where the local allies of Nazi Germany and those holding so many of the same ideas actually emerged triumphant in the postwar world.